FlyCounter: a simple software for counting large populations of small clumped objects in the laboratory - Arpit Yati; Sutirth Dey (BioTechniques, 2011)
While several software programs exist to count bacterial colonies on a Petri plate, no suitable solution is available for quick and reliable enumeration of small, live insects. We have written a program called FlyCounter that can obtain counts from images, even if insects are highly clumped in space. We also describe a simple and inexpensive system for anesthetizing and capturing high-quality images of the small insects. Taken together, our process is fast, fully automatic, and has a low percentage of error (∼1%–4% on average). Although we have tested our software on fruit flies, it should be simple to extend to other organisms of similar size.